Narratives of Power and the Power of Narratives: Transformation along the U.S.-Mexico Border - Cormier, Caroline (2010)
Using the Three Border Model developed by Mike Davis and Alessandra Moctezuma, this thesis presents a number of case studies focused on the narratives of power and transformation that continue to develop on the American side of the U.S.-Mexico border in the post-9/11 context. The first case study overviews the history of the U.S.-Mexico border in relation to the ongoing fortification of the physical boundary and its legal reification in federal policy. The second case study examines the exclusionary policies enacted by the state of Arizona as well as the anti-immigration agenda instituted by the Minuteman Project. The third case study examines the ways in which urban communities in the borderlands contest the material manifestations of the border present in their everyday lives. By surveying case studies at different sites and scales along the U.S.-Mexico boundary, this thesis challenges traditional conceptions of state power at the border.